Pemikiran Linguistik Ibnu Jinni: Kajian tentang Sifat Bunyi - Rahing, Nurhikmah; Haniah (Journal of Arabic Education and Linguistic, 2024)
The study of the characteristics of sound is an interesting area to explore due to itssignificant role in supporting the process of communication and Arabic language skills. Thisresearch aims to explain Ibn Jinni's linguistic thoughts on the characteristics of sound. This studyused the library research method with a qualitative descriptive approach. Library research methodis used to collecting data from existing references and literature that related to Ibn Jinni's linguisticthoughts. The results of this research consist of a study that includes Ibn Jinni's biography, IbnJinni's linguistic thoughts on the characteristics of sound, and the comparison of the theoriesregarding the characteristics of sound between Ibn Jinni and Sibawaih.